China-Africa relations in an era of great transformations - Farah, Abdulkadir Osman; Xing, Li (International political economy of new regionalisms series, 2013)
This collection juxtaposes a variety of approaches about China and Africa, and their interrelations seeking to go beyond early, simplistic formulations. It puts contemporary China-Africa relations in critical, comparative context and in doing so, it goes beyond descriptions of inter-regional trade and investment, large- and small-scale sectors, to ask whether structural change is underway.